Effect of implementation of Integrated Management of Neonatal and Childhood Illness (IMNCI) programme on neonatal and infant mortality: cluster randomised controlled trial. (21st March 2012) - Bhandari, Nita; Mazumder, Sarmila; Taneja, Sunita; Sommerfelt, Halvor; Strand, Tor A
Abstract : Objective To evaluate the Indian Integrated Management of Neonatal and Childhood Illness (IMNCI) programme, which integrates improved treatment of illness for children with home visits for newborn care, to inform its scale-up. Design Cluster randomised trial. Setting 18 clusters (population 1.1 million) in Haryana, India. Participants 29 667 births in intervention clusters and 30 813 in control clusters. Intervention Community health workers were trained to conduct postnatal home visits and women's group meetings; physicians, nurses, and community health workers were trained to treat or refer sick newborns and children; supply of drugs and supervision were strengthened. Main outcome measures Neonatal and infant mortality; newborn care practices. Results The infant mortality rate (adjusted hazard ratio 0.85, 95% confidence interval 0.77 to 0.94) and the neonatal mortality rate beyond the first 24 hours (adjusted hazard ratio 0.86, 0.79 to 0.95) were significantly lower in the intervention clusters than in control clusters. The adjusted hazard ratio for neonatal mortality rate was 0.91 (0.80 to 1.03). A significant interaction was found between the place of birth and the effect of the intervention for all mortality outcomes except post-neonatal mortality rate. The neonatal mortality rate was significantly lower in the intervention clusters in the subgroup born at home (adjusted hazard ratio 0.80, 0.68 to 0.93) but not in the subgroup born in a health facility (1.06, 0.91 to1.23) (P value for interaction=0.001). Optimal newborn care practices were significantly more common in the intervention clusters. Conclusions Implementation of the IMNCI resulted in substantial improvement in infant survival and in neonatal survival in those born at home. The IMNCI should be a part of India's strategy to achieve the millennium development goal on child survival. Trial registration Clinical trials NCT00474981 ; ICMR Clinical Trial Registry CTRI/2009/091/000715.